Enso phases and characteristics of rainfall and temperature in the Guarapuava region, southern Brazil (Research, Society and Development, 2020)
Enso (El Niño South Oscillation), is a system whose positive or negative phases can modifying the patterns of the variables that determine the climate in the southern hemisphere.  However, information about the influence on regional characteristics is still scarce, considering that there are site aspects that also interfere in the climate configuration. The objective of this work was to evaluate the behavior of temperature with the components of average, minimum and maximum and rainfall, under the influence of the Enos phases of the region of Guarapuava-PR in southern Brazil.Was used time serie with climatic data from 1976 to 2018. The statistical evaluation was performed by descriptive and multivariate analyzes with principal component analysis (ACP) and hierarchical cluster (HCA) with presentation of results in the form of heat maps. It was found that in periods of La Niña and neutrality, spring and summer are rainier compared to autumn and winter. With the predominance of El Niño, occur two rainfall periods, one in spring and early summer, and other in mid-autumn and early winter with higher rates compared to the first. The month of August presents the lowest levels of rainfall, regardless of the Enos phase.